1987
DOI: 10.3109/00016348709022043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bedrest in hospital on fetal outcome in pregnancies complicated by intra‐uterine growth retardation

Abstract: A prospective study was made to evaluate whether bedrest in hospital is beneficial in pregnancies where intra-uterine growth retardation (IUGR) was suspected. Diagnosis was based on routine fetometry at 32 weeks of gestation, in conjunction with general ultrasound screening. 107 patients with suspected IUGR-pregnancies were divided into two groups, 49 in a hospital bedrest group and 58 in an 'out-patient' group. Fifteen women in the bedrest group refused hospitalization, and 8 women in the out-patient group ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 15 publications
4
49
0
Order By: Relevance
“…Since no treatment has been demonstrated to be of benefit in growth restriction [75,76,77,78,79], assessment of fetal well-being and timely delivery remain as the main management strategy. The aim behind a clinical protocol for managing FGR is to combine existing evidence on various methods for monitoring fetal well-being in order to establish the risks of fetal injury or death, and to balance them against the risks of prematurity if the fetus is delivered.…”
Section: Clinical Management Of Fetal Growth Restriction and Small-fomentioning
confidence: 99%
“…Since no treatment has been demonstrated to be of benefit in growth restriction [75,76,77,78,79], assessment of fetal well-being and timely delivery remain as the main management strategy. The aim behind a clinical protocol for managing FGR is to combine existing evidence on various methods for monitoring fetal well-being in order to establish the risks of fetal injury or death, and to balance them against the risks of prematurity if the fetus is delivered.…”
Section: Clinical Management Of Fetal Growth Restriction and Small-fomentioning
confidence: 99%
“…We came across a single trial by Laurin in 1987, comparing birth weight among women on bed rest with ambulant but off work women. It was a small study involving 107 pregnant women, which reported that no differences were detected between bed rest and ambulatory management for fetal growth parameters (relative risk 0.43, 95% confidence interval: 0.15 to 1.27) and neonatal outcomes [18]. The study was too small to be accepted as concrete evidence for medical advice.…”
Section: Bed Rest In Impaired Fetal Growth and Reduced Afimentioning
confidence: 96%
“…The degree of intrauterine and neonatal morbidity was found to be reflected in patho logical changes of the fetal aortic blood veloc ity [24,25,27], Furthermore, a relationship has been found to exist between the mean fetal aortic velocity and the degree of fetal hypoxia, hypercapnia, acidosis, and hyperlactemia, as diagnosed in blood samples ob tained by cordocentesis in growth-retarded fe tuses [28],…”
Section: Doppler Ultrasoundmentioning
confidence: 99%
“…Since the late 70s, the Malmö Research Group [23,24,26,29] has systematically studied the fetal and uteroplacental blood flow in pregnancies suspected of IUGR. In one of the first prospective studies performed in Malmö during 1981 -1983, the blood veloc ity in the fetal thoracic descending aorta was serially recorded in 159 fetuses found to be SGA according to the routine fetometry dur ing the 33rd week of gestation [24], From this group, 74 infants were born with true IUGR.…”
Section: Doppler Study In Pregnancies Complicated By Iugrmentioning
confidence: 99%
See 1 more Smart Citation